Война всегда со мной - Бессонов Владимир Николаевич (Советская Россия, 1988)
Экземпляры: ф17/19/20 (20250115) / Инвентарный номер: 20175 / Цена: 0.40 / Сис.шифр: 63.3(2)722.4 / Авт.знак: Б 53 / ГРНТИ: 03 / ББК: 63.3(2)722.4